Anti-fraud measures in Southern Africa - Mykhalchenko, Nataliya (Capitalism and economic crime in Africa, 2024)
In response to the rising levels of fraud in many countries and the global economy more generally, public and private actors in both the global North and the global South have in recent years introduced initiatives in the name of countering fraud in the ‘private sector’. This briefing explores such anti-fraud measures in four countries in the Southern African region: Malawi, Botswana, South Africa and Zambia. Using online data (news outlets and reports on websites of private companies and governmental agencies), the authors provide a country-by-country account of some of the drivers and characteristics of these measures.